Interfacial Fracture Toughness of Multilayer Composite Structures - Her, S.-C.; Su, W.-B. (Проблемы прочности, 2015)
The interfaces in multilayer composite structures are susceptible to delamination due to the combination of active tensile and shear loads under operating conditions. A four-layer center crack composite beam in four-point bending is simulated to determine the interfacial fracture energy of the multilayer structure. The crack is propagating along the interface between the second and third layers. Based on the Euler–Bernoulli theory, the strain energy of the four-layer composite beam is derived. Strain energies before and after the propagation of the interfacial crack are calculated, which results in determining strain energy release rates. Analytical results for those rates are validated with the numerical data obtained by the finite element method. The effect of layer thickness of the composite beam on the interfacial fracture toughness is investigated through a parametric study.